Implications of late autism spectrum disorder diagnosis for females - Tomasula Martin, Lily, author; Hepburn, Susan, advisor; Ortega, Lilyana, committee member; Harman, Jennifer, committee member (Colorado State University. Libraries, 2023)
The purpose of this qualitative case study is to examine the implications of the timing of an Autism Spectrum Disorder (ASD) diagnosis for females, specifically its impact on psychological well-being. While it is well-known that females are less likely to be identified at young ages than their male counterparts, we know relatively little about the experiences or service needs of women with Autism Spectrum Disorder (ASD) who are identified later in life. Five women, ages 22 to 46 years who received a formal diagnosis after the age of 12 years, participated in an in-depth interview with a clinician focused on the impacts of a late Autism Spectrum Disorder diagnosis and the participants' overall well-being. Participants also completed a standardized self-report measure of psychological well-being. Participants then partook in a semi-structured interview to share their experiences of being a female with ASD. Responses from the questionnaires were summarized to provide a baseline understanding of participants' well-being while the semi-structured interview was analyzed to find themes in participant experiences. This qualitative case study includes a small number of participants, but we learned about the potential impacts of late diagnosis for females and their self-report of overall well-being. Both of which has implications for both research and practice.